Simone Atangana Bekono: Salomés Zorn (NL: Confrontaties) - Lammer, Christina

Sichtbarer Euklid? Zur Geometrisierung des Bildes in "De pictura" - Siemoneit, Johannes Gabriel (Leon Battista Alberti, "De pictura" (lat.). Kunsttheorie – Rhetorik – Narrative / Teoria dell'arte, retorica, narrative)

Die Zacher-Epitome. Änderungen, Erweiterungen, Auslassungen - Siemoneit, Johannes Gabriel (Der lateinische ›Alexanderroman‹ des Iulius Valerius)

Leon Battista Alberti: "Descriptio urbis Romae". Überlegungen zu Modernität und Entstehungskontexten, nebst lateinisch-deutscher Edition - Siemoneit, Johannes Gabriel

Gegenwartsprotestantismuskunde. 50 Jahre Liturgische Nacht. Katharina Herrmann: Gesungene Katechese. Kommunikation durch Popularisierung. Kulturelle Repräsentationen eines engagierten protestantischen Christentums im Neuen Geistlichen Lied (Religion in der Bundesrepublik Deutschland 11), Mohr Siebeck: Tübingen 2021, 412 S. - Schroeter-Wittke, Harald (Praktische Theologie)

DP-NMT: Scalable Differentially-Private Machine Translation - Igamberdiev, Timour; Vu, Doan Nam Long; Künnecke, Felix; Yu, Zhuo; Holmer, Jannik; Habernal, Ivan

LaCour!: Enabling Research on Argumentation in Hearings of the European Court of Human Rights - Held, Lena; Habernal, Ivan

Worship. Vor 300 Jahren erklang Bachs Magnificat - Schroeter-Wittke, Harald (Praktische Theologie)

Cryogenic reverse flow forming of AISI 304L - Arian, Bahman; Homberg, Werner; Kersting, Lukas; Trächtler, Ansgar; Rozo Vasquez, Julian; Walther, Frank (Materials Research Proceedings)
Abstract. Workpiece property-control permits the application-oriented and time-efficient production of components. In reverse flow forming, for example, a control of the microstructure profile is not yet part of the state of the art, in contrast to the geometry control. This is, due to several reasons, particularly challenging when forming seamless tubes made of metastable austenitic stainless AISI 304L steel. Inducing mechanical and/or thermal energy can cause a phase transformation from austenite to martensite within this steel. The resulting α’-martensite has different mechanical and micromagnetic properties, which can be advantageous depending on the application. For purposes of local property control, the resulting α’-martensite content should be measured and controlled online during the forming process. This paper presents results from the usage of a custom developed cryo-system and different application strategies to use liquid nitrogen as a coolant for local enhancement of the forming-temperature depending α’-martensite content.

La Belgique à travers les textes – Potenziale des sprachlichen und soziokulturel¬len Wissenserwerbs - Bürgel, Christoph; De Knop, Sabine (Belgien – anregend anders: Fachwissenschaft und Fachdidaktik untersuchen die Vielfalt der Sprachen, Literaturen und Kulturen in Belgien)